Study of Awareness, Enrollment, and Utilization of Rashtriya Swasthya Bima Yojana (National Health Insurance Scheme) in Maharashtra, India - Thakur, Harshad (Frontiers in Public Health, 2016)
Introduction – Government of India launched a social health protection programme called Rashtriya Swasthya Bima Yojana (RSBY) in the year 2008 to provide financial protection from catastrophic health expenses to Below Poverty Line households. The objectives of the current paper are to assess the current status of RSBY in Maharashtra at each step of awareness, enrolment, and utilisation. In addition, urban and rural areas were compared and Social, Political, Economic and Cultural (SPEC) factors responsible for the better or poor proportions especially for the awareness of the scheme were identified. Methods – The study followed mixed methods approach. For quantitative data, a systematic multi-stage sampling design was adopted in both rural and urban areas covering 6,000 households across 22 districts. For qualitative data, five districts were selected to conduct Stakeholder analysis, Focused Group Discussions and In Depth Interviews with key informants to supplement the findings. The data was analyzed using innovative SPEC–by–steps tool developed by Health Inc. Results – It is seen that that the RSBY had a very limited success in Maharashtra. Out of 6000 households, only 29.7% were aware about the scheme and 21.6% were enrolled during the period of 2010-12. Only 11.3% household reported that they were currently enrolled for RSBY. At least one case of hospitalization in last one year was reported by 1886 (33.1%) households but only 16 (0.3%) households could actually utilize the benefits during hospitalization. It is seen that at each step, there is increase in exclusion of eligible households from the scheme. The participants felt that such schemes didn’t reach their intended beneficiaries due to various SPEC factors. Discussion and Conclusion – The results of this study were quite similar to other studies done in the recent past. RSBY might still be continued in Maharashtra with modified focus along with good and improved strategy. Various other similar schemes in India can definitely learn few important lessons like – need to improve awareness, issuing prompt enrolment cards with proper details, achieving universal enrolment, ongoing and prompt renewal, ensuring proper utilization, etc. by proactively educating the vulnerable sections.